Isolation and characterization of cancer-associated fibroblasts in the tumor microenvironment of hepatocellular carcinoma - Kyoungdo Mun; Jiwon Han; Pureun Roh; Jonggeun Park; Gahee Kim; Wonhee Hur; Jeongwon Jang; Jongyoung Choi; Seungkew Yoon; Youngkyoung You; Hojoong Choi; Pilsoo Sung (Korean Liver Cancer Association, 2023)
Background/Aim Cancer-associated fibroblasts (CAFs) play an immunosuppressive role in the tumor microenvironment (TME) of human cancers; however, their characteristics and role in hepatocellular carcinoma (HCC) remain to be elucidated. Methods Nine tumor and surrounding liver tissue samples from patients with HCC who underwent surgery were used to isolate patient-derived CAFs. Cell morphology was observed using an optical microscope after culture, and cell phenotypes were evaluated using flow cytometry and immunoblotting. Cytokines secreted by CAFs into culture medium were quantified using a multiplex cytokine assay. Results CAFs were abundant in the TME of HCC and were adjacent to immune cells. After culture, the CAFs and non-tumor fibroblasts exhibited spindle shapes. We observed a robust expression of alpha-smooth muscle actin and fibroblast activation protein in CAFs, whereas alpha-fetoprotein, epithelial cell adhesion molecule, platelet/endothelial cell adhesion molecule-1, and E-cadherin were not expressed in CAFs. Furthermore, CAFs showed high secretion of various cytokines, namely C-X-C motif chemokine ligand 12, interleukin (IL)-6, IL-8, and C-C motif chemokine ligand 2. Conclusions CAFs are abundant in the TME of HCC and play a crucial role in tumor progression. These fibroblasts secrete cytokines that promote tumor growth and metastasis.